Lean nonalcoholic fatty liver disease and sarcopenia - Chen, Milian; Cao, Ying; Ji, Guang; Zhang, Li (Frontiers in Endocrinology, 2023)
Nonalcoholic fatty liver disease (NAFLD) has become one of the most common chronic liver diseases in the world. The risk factor for NAFLD is often considered to be obesity, but it can also occur in people with lean type, which is defined as lean NAFLD. Lean NAFLD is commonly associated with sarcopenia, a progressive loss of muscle quantity and quality. The pathological features of lean NAFLD such as visceral obesity, insulin resistance, and metabolic inflammation are inducers of sarcopenia, whereas loss of muscle mass and function further exacerbates ectopic fat accumulation and lean NAFLD. Therefore, we will discuss the association of sarcopenia and lean NAFLD, summarize the underlying pathological mechanisms, and propose potential strategies to reduce the risks of lean NAFLD and sarcopenia in this review.